Association between Sleep, Stress and BMI with Chrononutrition Behaviors among Military Personnel in Malaysia - Mohd Suki, Ain Suhana; Zaman, Mazuin Kamarul (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to find the association between sleep quality, stress level, and Body Mass Index (BMI) with the chrononutrition behaviors of military personnel. Six chrononutrition behaviors were assessed using the Chrononutrition Profile Questionnaire (CPQ). Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI) and perceived stress using the Perceived Stress Scale (PSS-10). The associations between chrononutrition behaviors and sleep quality, stress level, and BMI were determined using the Fisher exact test. Data was collected from 210 participants (median age: 27.5 years). Most military personnel, 62% (n=129) experienced moderate stress. Approximately 59.2% (n=122) demonstrated poor sleep quality. Out of six chrononutrition behaviors, sleep quality was significantly associated with evening eating (p=0.004) and night eating (p=0.028). Stress level was significantly associated with evening eating (p=0.051), night eating (p=0.019), and eating window (p=0.014). No association was found between chrononutrition behaviors and BMI of military personnel. Chrononutrition behaviors are associated with sleep quality and stress level but not body mass index in military personnel. Further understanding of sleep quality and stress among military personnel is imminent to prevent future weight issues concerning altered eating behaviors in this population.